The influence of physical activity on cognitive functions in the elderly population - Milanović, Anita; Đerić, Aleksandra; Pucar, Nadežda (PONS - medicinski časopis, 2024)
It is known that during the aging process, the likelihood of disturbance in cognitive psychic functions such as thinking and memory is increased. Dementia is the basis of age-dependent brain organosynthesis, which today present a serious public health problem. Some authors believe that regular exercise throughout life plays an important role in the prevention of dementia in old age, as well as the general improvement in cognitive abilities. Physical activity is a potential modulator of noradrenaline, serotonin and dopamine transmissions, both in the brain cortex and subcortical structures. It is possible, in this way, that regular physical activity indirectly influences the preservation and normal functioning of a brain cholinergic system that is vital to normal thinking, learning and memory. Also, aerobic muscle activity and exercise may potentially also affect other mental functions such as attention, perception, and emotions, or mood. Some physicians in primary and secondary health care often recommend exercising and practicing sports not only for the prevention of dementia, but also as an ancillary therapeutic agent for most organic and inorganic mental disorders. However, despite numerous studies, some aspects of the effects of physical activity on cognitive functions are still unknown. Molecular and cellular processes occurring in the limbic system during exercise are not sufficiently studied. Also, it is unclear whether and to what extent there are morphological changes in synapses and neuronal organization during physical activity, as well as whether these changes can prevent the development of dementia. The goal of research is to show the impact of physical activity and exercise on cognitive functions during the aging process, as well as the potential importance of exercise in the prevention of cognitive deficits in old age. The paper is written as a review paper. The database in which the search was performed was Medline, PubMed, Cobson. A review of the literature indicated the different views of the authors, as well as their agreement in the field, as well as the positive effects of regular exercise on the health of the elderly, including reduced mortality, reduced risk of falls and improved quality of life.